2005
DOI: 10.1158/0008-5472.can-05-0351
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Transformation by SEI-1 Is Associated with Chromosomal Instability

Abstract: Amplification of SEI-1, a cell cycle regulatory gene at 19q13.1, is commonly detected in ovarian cancer, suggesting a role in the pathogenesis of ovarian cancer. In the present study, the oncogenic potential of SEI-1 was shown by anchorageindependent growth and tumor formation in nude mice with SEI-1-transfected NIH 3T3 mouse fibroblast cells. Silencing of SEI-1 gene expression by small interfering RNAs in ovarian cancer cell line SKOV3 could inhibit cell growth as well as colony formation on soft agar. Chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…For example, overexpression of Aurora-A, a centrosome-associated kinase, can induce genetic instability as characterized by centrosome amplification, chromosome tetraploidization, and premature sister chromatid segregation (29). In our previous study, we found that the oncogenic role of SEI1 was associated with its effect on chromosomal instability (14). However, the molecular mechanism of how SEI1 induces genomic instability remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, overexpression of Aurora-A, a centrosome-associated kinase, can induce genetic instability as characterized by centrosome amplification, chromosome tetraploidization, and premature sister chromatid segregation (29). In our previous study, we found that the oncogenic role of SEI1 was associated with its effect on chromosomal instability (14). However, the molecular mechanism of how SEI1 induces genomic instability remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of SEI1 in SEI1-on cells was knocked down by RNA interference using small interfering RNAs (siRNA) against SEI1 as previously described (14). Double-stranded siRNAs were transiently transfected into SEI1-on cells using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instruction.…”
Section: Silencing Sei1 Expression By Rna Interferencementioning
confidence: 99%
See 1 more Smart Citation
“…In all, novel sequences were detected. Interestingly, some of these regions (1q41, 7p22, 8p11.23, 8q13.1, 8q22.3, 10q21.3, 10q24.32, 19q13.1, 20p11.23) have been described as amplified sequences in other human malignancies (Bruch et al, 1998;Curtis et al, 1998;Du Plessis et al, 1999;Larramendy et al, 2000;Pimkhaokham et al, 2000;Tang et al, 2002;Dai et al, 2003;Lukasova et al, 2004;Rao et al, 2004). The RLGS data does not allow us to discriminate between DNA copy number gains that have integrated at the location of the original sequence or extra DNA localized in extrachromosomal double minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the SEI-1 gene is highly expressed in carcinomas from pancreatic (2), lung (3), and ovarian tissues (4), suggesting that p34 SEI-1 functions as an oncoprotein. Interestingly, recent studies have shown that p34 is capable of oncogenic transformation of mouse fibroblasts (5). However, it is not clear whether p34…”
Section: Introductionmentioning
confidence: 99%